An Euler-Euler model for mono-dispersed gas-particle flows incorporating electrostatic charging due to particle-wall and particle-particle collisions. (6th April 2019) - Ray, M.; Chowdhury, F.; Sowinski, A.; Mehrani, P.; Passalacqua, A.
Highlights: Two-fluid model with charge generation and transport model. Validation of contact charging model against experiments involving polyethylene particles in bubbling fluidized beds. Prediction of charge density in the fluidized bed with insulating particles. Prediction of wall sheeting. Abstract: A computational model for the prediction of triboelectric charging in gas-solid fluidized beds is developed in the context of the Euler-Euler two-fluid model with kinetic theory closures for the description of the particulate phase. Sub-model for charge transfer due to particle-wall collisions is obtained consistently with the boundary conditions of Johnson and Jackson (1987), and assuming the model of Matsusaka et al. (2000) for charge transfer during a single collision. Similarly, a sub-model for charge diffusion due to particle-particle collisions is developed based on the kinetic theory of granular flow of Jenkins and Savage (1983), and the aforementioned charging model. The Eulerian charging model is then coupled to the two-fluid model, with kinetic theory closures which are available in the OpenFOAM® computational toolbox for fluid dynamics. The model is tested to simulate the effect of polyethylene particle size (362, 462, 550 μm) in the electrification process, and is validated against experimental findings (Sowinski, 2012; Sowinski et al., 2012). The order of magnitude of charge densities in different regions of the bed, predicted by the model, was coherent with the experimental results. The model also predicted that particles larger than 425 μm would not stick to the column wall, which acceptably agreed with the experimental observation that particles larger than 600 μm did not adhere to the wall surface.